Challenges and Opportunities of Indonesia's Macroeconomy in the Digital Era - Andhini Sovi Hidayanti; Syamsul Arifin; Irviandi Yudhotomo (CV Pena Jaya Pers, 2025)
Digital has become a key pillar in Indonesia's macroeconomic structure by 2026. This research aims to analyze the dynamics of challenges and opportunities that arise along with the integration of digital technology in national economic activities. Using the latest secondary data-based descriptive qualitative methods, this study found that the acceleration of the digital economy provides great opportunities for Gross Domestic Product (GDP) growth through improving the efficiency of the MSME sector, expanding financial inclusion, and strengthening the creative economy. However, on the other hand, Indonesia faces significant challenges in the form of digital infrastructure gaps between regions, increasing cybersecurity risks, and the urgent need for workforce reskilling to face automation. The results of the analysis show that the synergy between adaptive monetary policy and digital fiscal transformation is key to maintaining macroeconomic stability. This paper concludes that strengthening data protection regulations and equitable distribution of broadband internet access is an absolute prerequisite for Indonesia to optimize the potential of the digital economy to achieve sustainable economic growth targets in the future.